2021
DOI: 10.1007/s40596-021-01513-z
|View full text |Cite
|
Sign up to set email alerts
|

Attitude Towards Suicide and Help-Seeking Behavior Among Medical Undergraduates in a Malaysian University

Abstract: Objective The attitude of medical personnel towards suicide may influence the outcome of suicidal-patients management. This study aimed to determine the attitudes of medical undergraduates towards suicide and its association with their help-seeking behavior. Methods A cross-sectional study involving 290 medical undergraduates was conducted in a Malaysian university. The questionnaires on the attitude towards suicide and general help-seeking behavior were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Faculty members should be trained to recognize red flags in students who exhibit signs of being cyberbullied. [19][20][21]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Faculty members should be trained to recognize red flags in students who exhibit signs of being cyberbullied. [19][20][21]…”
Section: Discussionmentioning
confidence: 99%
“…IeJSME 2023 17 (2): [18][19][20][21][22][23][24][25][26] To date, there has been limited data on cyberbullying among Malaysian medical students, with only one such study in a public medical university of Malaysia showing a high prevalence of 24.4% cyberbullying over the past six months. 5 The prevalence of mild depression among cyberbullied victims was 34.0%.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Malaysian students population are an at-risk population for suicidal behavior ( 10 ). More studies on the suicide rate in other countries have found a higher suicide rate among healthcare workers and healthcare students compared to other professions ( 12 , 19 22 ) due to multiple factors. This has also been reflected in a Malaysian study.…”
Section: Introductionmentioning
confidence: 98%
“…Being school leavers put them at high risk of suicide ( 6 10 ) and it has also been reported that they are the group with the highest risk to have mental health problems ( 11 ). Furthermore, these students, especially Malaysian healthcare students ( 12 ) are less likely to seek professional help when depressed ( 13 – 15 ) or having suicidal thoughts.…”
Section: Introductionmentioning
confidence: 99%
“…Students are the vulnerable group for the study of help-seeking due to their high prevalence of anxiety. Several studies suggested there is a need to focus on reducing the stigma surrounding suicide to influence help-seeking attitudes among the students at risk 20 , 21 . In addition, help-seeking behavior (HSB) toward anxiety and its associated factors are pivotal in designing effective community-based mental health interventions 9 .…”
Section: Introductionmentioning
confidence: 99%